A CIRCUMSTANTIAL ANALYSIS ON EVIDENCE AND GEOLOGICAL INFORMATION BASED ROUTING PROTOCOL INUNDERWATER SENSOR NETWORKS (Journal of Pharmaceutical Negative Results, 2023)
In recent days, underwater wireless sensor networks (UWSNs) are now a prominent topic for research. These systems mayperform a variety of submarine tasks, like tidal, acoustic, hydrological, and seabed navigation. UWSNs, however, are subject to a number of restrictions and objections, such as significant sea intrusion and noise, lengthy propagation latency, a limitedradio spectrum, graphical model architecture, and energy storage restrictions for sensor nodes. The creation of network topologies is one approach to solving these issues. Information may be efficiently sent across the system from the expert node to the target node using a communication scheme. The submarine routing protocols for UWSNs are examined in this paper. Existing underground route accords may be categorized into three types and they are energy based , data based and geographic based protocols. In this paper we have discussed the evidence-established and geological information-establishedcovenants. In addition, we discuss underwater routing methods' research obstacles and potential possibilities, which can aid future exploration.